Penyalahgunaan Keadaan Pada Asas Itikad Baik dalam Perjanjian Kerja Sama Bagi Hasil - Muhammad Adhi Utomo; Tundjung Herning Sitabuana (Universitas Islam Balitar, Blitar, 2023)
One of the cooperative systems in business that is commonly practiced is the profit-sharing cooperation system. In cooperation, it is common for two or more parties to enter into an agreement. One of the legal principles of the agreement is the principle of good faith as stated in Article 1338 paragraph (3) of the Civil Code which emphasizes the necessity for the parties to carry out the agreement in good faith. Through normative legal research with qualitative analysis techniques, a study is produced that the abuse of circumstances is one of the causes of the production sharing agreement being canceled. Misuse of conditions in a profit-sharing cooperation agreement is an act motivated by an imbalance between the parties to the agreement, with an indication that a strong party takes advantage of the position of a weak party.